Joint Sliding-Mode Controller and Observer for Vehicle Platoon Subject to Disturbance and Acceleration Failure of Neighboring Vehicles - Zhu, Yongxin; Li, Yongfu; Zhu, Hao; Hua, Wei; Huang, Gang; Yu, Shuyou; Li, Shengbo Eben; Gao, Xinbo (IEEE transactions on intelligent vehicles, 2023)
This article designs a jointly distributed adaptive sliding-mode controller (DASMC) and disturbance observer (DO) for a heterogeneous platoon of connected vehicles (CVs) subject to disturbance and acceleration failure of neighboring vehicles under the multifold common communication topologies. To circumvent the effects of disturbance and acceleration failure of neighboring vehicles, the disturbance arising from the vehicle heterogeneity and nonlinearity as well as the acceleration of neighboring vehicles is jointly estimated as a lumped disturbance by a DO. In particular, the sliding-mode surface with adaptive law is designed based on the defined lumped errors to support the diversity of communication topologies. Then, the DASMC with DO is designed according to the vehicle dynamic model. Meanwhile, the stability of the designed DASMC with DO is analyzed based on the Lyapunov technique. In addition, the string stability of the CV platoon is proved. Finally, the capabilities of the developed control scheme are demonstrated by the simulation and experiment under different communication topologies and compared with existing methods.